Role of moral identity and moral courage characteristics in adolescents’ general and situation-specific expressions of the tendency to be a moral rebel - Sonnentag, Tammy L. (Kansas State University, 2014)
The term “moral rebel” describes an individual who refuses to comply, stay silent, or conform to others when doing so would compromise his/her values (Monin, Sawyer, & Marquez, 2008). Preliminarily, this study examined the extent to which adolescents themselves, their peers, and their teachers agree in their ratings of adolescents’ general expressions of the tendency to be a moral rebel, tendencies to possess a moral identity (i.e., prioritize morality as an important part of identity), and tendencies to possess moral courage characteristics (i.e., qualities that motivate individuals to take action on their beliefs and values). As a theoretical and empirical extension of previous research (see Sonnentag & Barnett, 2013), the present study's primary purpose was to examine the interactive and independent roles of moral identity and moral courage characteristics in adolescents’ general and situation-specific (i.e., caring, just, and brave) expressions of the tendency to be a moral rebel. With regard to the interactive role of moral identity and moral courage characteristics, the present study examined (1) if relatively high levels of various general moral courage characteristics (i.e., Self-Esteem, [Low] Need to Belong, Self-Efficacy, Assertiveness, Social Vigilantism) encourage adolescents to act on their moral identities to display the general and situation-specific expressions of the tendency to be a moral rebel and (2) if relatively high levels of situation-specific moral courage characteristics (i.e., Empathic Concern, Justice Sensitivity, Willingness to Take Action in Physically Dangerous Situations) encourage adolescents to act on their moral identities to display the corresponding situation-specific (i.e., caring, just, and brave, respectively) expressions of the tendency to be a moral rebel. As predicted, results revealed significant positive correlations among the self-report, peer, and teacher ratings of adolescents' (1) general expressions of the tendency to be a moral rebel, (2) tendencies to possess a moral identity, and (3) tendencies to possess general moral courage characteristics. These significant positive inter-correlations emerged for the entire sample as well as for the male and female participants when they were considered separately. Contrary to prediction, moral identity (when considered independently and in combination with the general and situation-specific moral courage characteristics) did not consistently predict the general nor situation-specific expressions of the tendency to be a moral rebel. Furthermore, although the general moral courage characteristics did not consistently predict the adolescents’ caring, just, and brave expressions of the tendency to be a moral rebel, all of the indices of the adolescents' general moral courage characteristics (i.e., Self, Peer, and Teacher ratings; Self-Esteem, [Low] Need to Belong, Self-Efficacy, Assertiveness, Social Vigilantism) positively predicted the adolescents’ self-reported general tendency to be a moral rebel. Finally, two of the situation-specific moral courage characteristics (i.e., Empathic Concern and Willingness to Take Action in Physically Dangerous Situations) were found to be positively associated with the corresponding situation-specific (i.e., caring and brave, respectively) expressions of the tendency to be a moral rebel. The implications and limitations of the present findings, as well as directions for future research on the topic of moral rebelliousness in adolescents, are addressed
Keywords: Moral rebel; Psychology (0621)